2007
DOI: 10.1177/070674370705201104
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Memory Bias and the Symptoms of Schizophrenia

Abstract: Much of the research on episodic memory in schizophrenia spectrum disorders has focused on memory deficits and how they relate to clinical measures such as outcome. Memory bias refers to the modulatory influence that state or trait psychopathology may exert on memory performance for specific categories of stimuli, often emotional in nature. For example, subjects suffering from depression frequently have better memory for negative stimuli than for neutral or positive ones. This dimension of memory function has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 107 publications
0
14
0
Order By: Relevance
“…However, it is of note that the possible effects of changes in state psychopathology on memory specificity are not confined to changes in state rumination. Other studies outside of the domain of memory specificity have reported an association between changes in mood, and the negative and positive symptom dimensions of schizophrenia, and changes in episodic memory performance amongst people with schizophrenia (Lepage, Sergerie, Pelletier, & Harvey, 2007). No study has yet examined this directly by inducing change in rumination or affect, or in measuring natural longitudinal changes in these variables in schizophrenia patients to examine whether this is associated with changes in specificity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is of note that the possible effects of changes in state psychopathology on memory specificity are not confined to changes in state rumination. Other studies outside of the domain of memory specificity have reported an association between changes in mood, and the negative and positive symptom dimensions of schizophrenia, and changes in episodic memory performance amongst people with schizophrenia (Lepage, Sergerie, Pelletier, & Harvey, 2007). No study has yet examined this directly by inducing change in rumination or affect, or in measuring natural longitudinal changes in these variables in schizophrenia patients to examine whether this is associated with changes in specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although activity scheduling is part of BA treatments and the PEPS intervention, these treatments lack a thorough and objective analysis of pleasurable experiences. This is important, as anhedonia is characterized by difficulties recalling pleasurable experiences (Lepage, Sergerie, Pelletier, & Harvey, 2007), and therefore, anhedonic individuals may not be able to recall all activities that they enjoy.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] It is not clear, however, whether they can benefit or not from a memory boost for social information. It is possible that an altered memory of social information in patients with schizophrenia may be associated with abnormalities in different neural regions than those typically associated with emotional memory deficits (i.e., amygdala).…”
Section: Introductionmentioning
confidence: 99%